Anxiety vs. Understanding: How Reading Stress Affects Language Learners' Comprehension? - Jannah, Aniatul; Juniardi, Yudi (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2025)
This study examines the relationship between students' foreign language reading anxiety and their reading comprehension. It involved 28 eleventh-grade students from SMK Yarsi Medika in Kabupaten Tangerang. The research used a correlational design, with the English Foreign Language Reading Anxiety Inventory (EFLRAI) to measure reading anxiety and a reading comprehension test to evaluate students' abilities. The findings showed that most students experienced moderate levels of reading anxiety, with bottom-up anxiety (related to unfamiliar vocabulary) being the primary cause. The correlation analysis revealed a weak negative relationship between reading anxiety and reading comprehension (correlation coefficient = 0.053), which was not statistically significant (p = 0.788). These results suggest that reading anxiety does not have a significant impact on reading comprehension in this group of students. The study concludes that although students feel anxious during reading activities, this anxiety does not notably affect their ability to understand English texts.